Efficacy of nutrition education for the increase of symbiotic intake on nutritional and metabolic status in schizophrenic spectrum disorders: A two-arm protocol - Sevillano-Jiménez, Alfonso; Molina-Recio, Guillermo; García-Mellado, Juan Antonio; García-Rodríguez, María; Molina-Luque, Rafael; Romero-Saldaña, Manuel (Frontiers in Nutrition, 2022)
Background: The microbiota plays a vital role in the two-way communication between the gastrointestinal tract and numerous neuropsychiatric disorders, such as schizophrenia. Besides, the microbiota modulation through the use of psychobiotics (prebiotics and probiotics with nutraceutical action) is related to the improvement of the physical and psychopathological health. The objective to this study was to test the efficacy of prebiotic/probiotic dietary modulation in patients diagnosed with schizophrenia, attending to the nutritional and cardio-metabolic impact. Methods: Two-arms, double-blind, randomized in balanced blocks clinical trial of six months of intervention, will be developed in a group of 50 individuals. The control group will received conventional dietary advice individually. In the intervention group, will be established of an individual program of dietetic-nutritional education with high prebiotic and probiotic content. Data will be collected on the psychopathological state, and blood test (at the beginning, at three and six months). The estimation of intestinal microbiota and the usual nutritional pattern will also be assessed at the beginning and six months, using a stool test. To evaluate the degree of adherence, the intervention group will fill a specific weekly record of the main dishes/food consumed. Anthropometric parameters will also be analyzed monthly. Discussion: The study is anticipated to establish feasibility an adequate dietary modulation with a high simbiotic content, leads to a significant improvement in the nutritional status and cardio-metabolic. Furthermore, it is presumed to reach a degree of evidence that allows establishing nutritional management as an effective therapeutic intervention in the psychopathological treatment of patients with schizophrenia spectrum disorders. Trial registration: Clinical Trials ID: NCT04366401. First Submitted: April 28, 2020 (https://clinicaltrials.gov/). This research also has the permission of the Zamora Health Area Drug Research Ethics Committee (No. reg. 468). Keywords: Prebiotic; Probiotic; Schizophrenia Spectrum and Other Psychotic Disorders; Diet Therapy; Mental Health.